Community Empowerment in Developing Kampoeng Lama Tourism Village as an Educational Tourism Destination - Widya Octovia Rini Simanjuntak; Muhammad Halfi Indra Syahputra (Cita Konsultindo Research Center, 2021)
Tourism community empowerment has always been the main issue. Community empowerment in developing rural tourism have to contribute to public prosperity. Empowerment can be achieved through the development of education tourism. This research was conducted in Desa Wisata Kampoeng Lama Kabupaten Deli Serdang, North Sumatera. The methodology used is descriptive with qualitative research. Data collection method used is observation field, interviews and documentation. This study aims to determine the form of community empowerment, the obstacles faced during the empowerment process and the results of empowerment in developing educational tourism in Desa Wisata Kampoeng Lama. The primary data source was obtained from purposive sampling. From the results of this study, it was concluded that the community empowerment carried out to develop educational tourism had not run optimally so that the benefits had not been felt by the surrounding community.